2011
DOI: 10.1007/s10608-011-9396-5
|View full text |Cite
|
Sign up to set email alerts
|

Attention to Emotional Images in Previously Depressed Individuals: An Eye-Tracking Study

Abstract: Depression and dysphoria are associated with attention and memory biases for emotional information (Williams et al. 1997; Yiend in Cogn Emot 24:3-47, 2010), which are postulated to reflect stable vulnerability factors for the development and recurrence of depression (Gotlib and Joormann in Annu Rev Clin Psychol 6:285-312, 2010). The present study looked for evidence of attention and memory biases in individuals with a self-reported history of depression, compared to individuals with dysphoria and individuals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 35 publications
7
62
2
Order By: Relevance
“…Partly consistent with theory, Sears and colleagues (2011) found that RMDs (N=15) oriented their overt attention (eye-tracking data) to depression-related stimuli more than NDCs (N=38), although they did not orient their attention differently to positive stimuli; RMDs did however express fewer fixations and shorter overall fixation time on positive stimuli compared to NDCs. Yet, RMDs did not make more fixations or express longer overall fixation time on depression-related stimuli than NDCs (Sears, Newman, Ference, & Thomas, 2011). However, other eye-tracking research reported that current depression (N=21), but not RMD (N=21), was associated with a loss of elaborative overt attentional processing of positive stimuli that characterizes healthy controls (N=21) (Isaac, Vrijsen, Rinck, Speckens, & Becker, 2014).…”
Section: Attentional Bias Temporal Dynamics In Remitted Depressionmentioning
confidence: 77%
“…Partly consistent with theory, Sears and colleagues (2011) found that RMDs (N=15) oriented their overt attention (eye-tracking data) to depression-related stimuli more than NDCs (N=38), although they did not orient their attention differently to positive stimuli; RMDs did however express fewer fixations and shorter overall fixation time on positive stimuli compared to NDCs. Yet, RMDs did not make more fixations or express longer overall fixation time on depression-related stimuli than NDCs (Sears, Newman, Ference, & Thomas, 2011). However, other eye-tracking research reported that current depression (N=21), but not RMD (N=21), was associated with a loss of elaborative overt attentional processing of positive stimuli that characterizes healthy controls (N=21) (Isaac, Vrijsen, Rinck, Speckens, & Becker, 2014).…”
Section: Attentional Bias Temporal Dynamics In Remitted Depressionmentioning
confidence: 77%
“…Regarding the nature of emotional biases in individuals with BD, the biases toward happy and sad images were statedependent. On the one hand, similarly to MDD patients (Kellough et al, 2008;Leyman et al, 2011;Sears et al, 2010Sears et al, , 2011Ellis et al, 2011), BD patients in the depressive phase paid less attention to the happy images than the control group, as deduced from the fixation time and the fixation frequency found for these images. On the other hand, although BD patients in the depressive phase paid more attention to sad images than the healthy controls in percent of fixations (27% versus 25%, respectively), this difference did not reach statistical significance-this difference was significant in previous eye-tracking studies in individuals with MDD (Eizenman et al, 2003;Kellough et al, 2008).…”
Section: Stimulus Category Number Of Fixations (% Of Total)mentioning
confidence: 93%
“…Of particular relevance here is the free-viewing task, in which participants are required to focus on a central fixation point, and then asked to scan/re-scan several stimuli (2-4 stimuli, e.g., images, faces, or words) presented simultaneously, depicting differing valences (happy, sad, threat or neutral) for around 10-30 s. A number of studies assessed the maintenance of attention over the entire trial (e.g., by measuring the total fixation time on each image; see Eizenman et al, 2003;Kellough et al, 2008;Leyman et al, 2011;Sears et al, 2010Sears et al, , 2011Ellis et al, 2011). Depressed individuals attended less to happy stimuli than nondepressed individuals (i.e., an "anhedonic bias" was found; Kellough et al, 2008;Leyman et al, 2011;Sears et al, 2010Sears et al, , 2011Ellis et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…58 Previous research has shown that those with MDD have difficulties with attention and information processing when an eye tracking device was used. [62][63][64] Future studies can apply this method to investigate if culture influences the way in which adults with MDD process facial emotions. Furthermore, there is a wide range of medical research showing that MDD is linked to inflammatory response.…”
Section: Resultsmentioning
confidence: 99%